Methods of Rehabilitation of Children through Eastern Martial Arts and their Impact on Health - Georgiev, Yordan; Nedev, Nikolay; Ivanova, Elena; Nikolova, Donka; Popova, Monika (International Journal of Child Health and Nutrition, 2025)
Purpose: This study aimed to evaluate the effectiveness of Eastern martial arts as a rehabilitation method for children and their impact on health outcomes. Material and Methods: The research methodology involved a comprehensive three-month intervention program conducted at specialized rehabilitation centers in Bulgaria, including the National Sports Academy “Vassil Levski” Rehabilitation Center in Sofia and the Varna Martial Arts Therapy Center. The study included 128 children aged 5-17 years with various conditions who participated in twice-weekly, 60-minute adapted martial arts sessions. Physical parameters were evaluated using standardized tests, including the Bruininks-Oseretsky Test, astrometric platforms, and dynamometers, while psychological outcomes were assessed using validated scales. Results: The analysis revealed significant physical improvements, with static balance enhancement of 54.9%, dynamic balance improvement of 18.2%, and overall motor proficiency increase of 26.3% across different martial arts disciplines. Psychological assessments demonstrated 50% improvement in emotional control, 50.8% enhancement in attention span, and also 46.2% reduction in anxiety levels. The implementation of martial arts-based rehabilitation programs achieved 82.6% adherence rates and 85.3% therapeutic goal achievement, with full integration models showing the highest success rates. Long-term monitoring revealed sustained improvements in cardiovascular fitness, with enhanced oxygen utilization and better recovery rates after physical exertion. Cross-environmental behavioral improvements showed 60.9% reduction in behavioral incidents at home and 56.4% in school settings. Conclusion: These findings indicate that Eastern martial arts serve as effective complementary approaches in children’s rehabilitation programs in Bulgaria, offering comprehensive benefits for both physical and psychological development when properly implemented and adapted to specific therapeutic needs.